Proyecto de factibilidad para la producción de café orgánico de algarroba en la ciudad de Loja - Angamarca Masache, Patricio Ramiro (2015)
This paper analyzes the viability of installing a micro production and marketing of organic coffee carob in the city of Loja. The study began with market research, where there is unmet demand in the market for such services is identified, this market research unveiled acceptance of Loja potential customers, which supports the feasibility of the project. Within the Technical Study determinants analysis for determining the location, production capacity, Manpower requirements, Raw Materials, Materials, Supplies and technological equipment the company needs to start his business was conducted. The optimum location for the project is set to install in the center of the city of Loja, for the commercial advantage that would be obtained on competition and rapid positioning that could acquire the company, you will have a local rented for customer service and the development of their products. The staff will be required for the production and marketing operations of the company is made up of the Manager, Administrator, Head of production and marketing, janitors, handymen and winemaker. From Financial Study budget investment value amounting to $ 37,499.55, of which 60.68% are fixed assets, deferred assets to 7.14% and 32.18% represent working capital was established. This investment will be financed through its own resources by 40% ($ 14,999.82) and a loan from Banco del Pichincha equal to 60% ($ 22,499.73) remaining of the total investment. Estimated earnings reflect increasing values depending on the amount of product sold in each year. The values grow from $ 174,143.10 in the first year of operation to $ 961,106.90 in the fifth year, considering a price of about $ 5.00 per unit carob coffee 250g. The value of the Internal Rate of Return (IRR) of the project without considering the financing was funded 48.75% and 43.5%. The net present value of unfunded defined project worth $ 1,189,305.26 and $ 73,177.38 financing. Financial indicators obtained demonstrate the feasibility of this study. The project reported a greater sensitivity to decreased sales by 5% and increased 20% cost. The increase in wages and salaries does not greatly affect the study. So it is recommended to increase advertising and strategic alliances with suppliers to minimize costs. As a general conclusion the viability and feasibility of this project is determined, it is an investment that ensures the return on invested capital, obtaining profitability from the first year of operations at the start for the creation of the company recommends "Organic Coffee Carob DON DUCK "